الفكر الإصلاحي والمقاومة الثقافية عند أحمد رضا حوحو (1911-1956) من خلال القصة القصيرة - بعلي, زوبير (University of Eloued جامعة الوادي, 2022)
يعتبر أحمد رضا حوحو من روّاد الأدب الجزائري الحديث، وقد عُرف أكثر ما عُرف بالتأليف والكتابة في جنس أدبيّ تميّز به وهو القصة القصيرة، وقد استغل أحمد رضا حوحو هذا الجنس الأدبي في الحركة الإصلاحية في الجزائر، كيف لا وهو أحد الفاعلين في جمعية العلماء المسلمين الجزائريين التي حملت لواء الإصلاح في القرن 19م، فحملت مجموعته القصصية: "نماذج بشرية"، "مع حمار الحكيم"، "غادة أمّ القرى"، وكذا "صاحبة الوحي".. أفكارا إصلاحية تناولت بالنقد الذهنيات البالية التي كانت تسود المجتمع آنذاك كاحتقار المرأة وعدم تعليمها، وكذا الدروشة واستغلال النّاس تحت عباءة التديّن وإظهار التنسّك، كما انتقد مناهج التعليم في وقته. ويظهر البعد الإسلامي حاضرا في قصصه، والدعوة إلى ترسيخ الثقافة الإسلامية الأصيلة والاهتمام بالتعليم للوقوف في وجه الغزو الثقافي للاستعمار الذي عمل على تجهيل الشعب واحتقاره. . Abstract : Ahmed Ridha Houhou (1911- 1956) is considered as one of the pioneers of the Algerian modern literature. Well-renowned as a short story writer, he used this literary genre in the Reformist Movement in Algeria lead by the Algerian Muslim Scientists' Association that he was an activist in. His story collection " Namadhidge Bachariya ", " Ma'a Himar Elhakim ", " Ghada Oum Elqora", " Sahibat Elwahi " and other ones contained reformative thoughts criticising old mentalities which were dominant in then societies such as trivializing women and depriving them from education, as well as fake Sufism that exploited people under the cover of religion. He also criticised the then educational curricula. The Islamic dimension is well-present in his story-telling. He sought the consolidation of the authentic Islamic culture as well as education to hinder the colonial cultural invasion which promoted ignorance and despised the people.
Ahmed Ridha Houhou's(1911-1956) Reformative thoughts and Cultural Resistance Through The Short Story
مداخلة
Keywords: القصة القصيرة؛ البناء الاجتماعي؛ الموروث الثقافي؛ البعد الإسلامي؛ البعد الإصلاحي; The Short Story; the social fabric; the cultural heritage; the Islamic dimension; the reformist dimension.